Always Checking: Constant Connectivity and Fear of Missing Out among Generation Z Social Media Users - Fitri Norhabiba; Hasna Nur Lina; Mutiah (Jogjakarta Communication Conference (JCC), 2026)
Social media's rapid proliferation has engendered a pervasive culture of constant connectivity, particularly among Generation Z—digital natives immersed in hyper-connected environments from birth. Although perpetual online presence facilitates instantaneous communication and information access, it simultaneously precipitates psychological distress, including fear of missing out and digital anxiety. This study rigorously examines the causal relationship between constant connectivity and FOMO among Generation Z social media users, addressing a critical gap in understanding the emotional toll of digital nativity. A quantitative survey of 130 university students in Indonesia, was analyzed using Partial Least Squares Structural Equation Modeling, which robustly delineates structural paths and causal influences among latent constructs. Empirical results unequivocally confirm that constant connectivity exerts a significant positive effect on FOMO, with path coefficients indicating strong predictive power. A substantial majority (more than 70%) of respondents exhibited compulsive notification-checking and persistent online vigilance—emblematic of an entrenched